2018
DOI: 10.1016/j.bone.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Low bone toughness in the TallyHO model of juvenile type 2 diabetes does not worsen with age

Abstract: Fracture risk increases as type 2 diabetes (T2D) progresses. With the rising incidence of T2D, in particular early-onset T2D, a representative pre-clinical model is needed to study mechanisms for treating or preventing diabetic bone disease. Towards that goal, we hypothesized that fracture resistance of bone from diabetic TallyHO mice decreases as the duration of diabetes increases. Femurs and lumbar vertebrae were harvested from male, TallyHO mice and male, non-diabetic SWR/J mice at 16weeks (n≥12 per strain)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 54 publications
7
16
0
Order By: Relevance
“…For example, overexpression of lysyl hydroxylases—which regulate the organization of enzymatic cross‐links in type 1 collagen—can change the molecular packing of collagen fibrils and lead to abnormal nucleation of hydroxyapatite crystals, ( 55 ) whereas inhibition of lysyl oxidase in rats decreased the concentration of mature collagen cross‐links by ~45% decreased femoral bending strength by 26% compared with controls. ( 58 ) Although the KKay mouse, ( 59 ) TallyHo mouse, ( 60 ) and ZDSD rat ( 61 ) similarly exhibit greater tissue mineral content (in contrast to mice fed a high‐fat diet ( 62 ) ), these models have limited ability to inform how progressive glycemic derangement alters tissue‐level and structural properties in bone because no rodent model captures (i) all of the observed changes in compositional properties, as reviewed recently ( 63 ) or (ii) the complexity of human T2DM (eg, longer duration, later onset). Together, the compositional differences identified here highlight several possible areas for future studies of the mechanisms of altered skeletal integrity with impaired glucose control and T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…For example, overexpression of lysyl hydroxylases—which regulate the organization of enzymatic cross‐links in type 1 collagen—can change the molecular packing of collagen fibrils and lead to abnormal nucleation of hydroxyapatite crystals, ( 55 ) whereas inhibition of lysyl oxidase in rats decreased the concentration of mature collagen cross‐links by ~45% decreased femoral bending strength by 26% compared with controls. ( 58 ) Although the KKay mouse, ( 59 ) TallyHo mouse, ( 60 ) and ZDSD rat ( 61 ) similarly exhibit greater tissue mineral content (in contrast to mice fed a high‐fat diet ( 62 ) ), these models have limited ability to inform how progressive glycemic derangement alters tissue‐level and structural properties in bone because no rodent model captures (i) all of the observed changes in compositional properties, as reviewed recently ( 63 ) or (ii) the complexity of human T2DM (eg, longer duration, later onset). Together, the compositional differences identified here highlight several possible areas for future studies of the mechanisms of altered skeletal integrity with impaired glucose control and T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Raman sub-peaks of the Amide I band of bone are also sensitive to the disruption of collagen enzymatic crosslinking 46 , tissue aging 47 , degree of mineralization 48 , ionizing radiation 49,50 , and hydration 45 . More recently, the ~I 1670 /I 1640 ratio was found to be higher in diabetic mouse bone with lower toughness compared to non-diabetic mice bone with higher toughness 51 , implying it could be sensitive to advanced glycated end-products (AGEs), although fluorescence AGEs and pentosidine, an AGE crosslink, were not different between the groups. The ~I 1670 /I 1640 ratio was also recently reported to be sensitive to in vitro glycation of human cortical bone as well 52 .…”
Section: Discussionmentioning
confidence: 99%
“…In animal models of T2DM, some studies have reported increased AGE content in the bone tissue (48, 49), while other studies have reported no difference in AGEs but alterations in the collagen structure (50) and increased collagen maturity (51). Since levels of AGEs in the bone tissue cannot be measured noninvasively in patients, surrogates, such as serum or urine levels, are typically used.…”
Section: Structural and Materials Properties Of Bone In T2dmmentioning
confidence: 99%